2013
DOI: 10.5851/kosfa.2013.33.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vivo Colonization Screening of Probiotic Bacteria Isolated from Human Infants using Caenorhabditis elegans Surrogate Host

Abstract: The ability of probiotics to adhere to the intestinal epithelium likely plays an important role in their colonization of the gastrointestinal tract. Here, we performed high-throughput screening (HTS) for suitable characteristics of potential probiotic bacteria using attachment and colonization ability through a C. elegans surrogate in vivo model. A total of 100 strains of lactic acid bacteria (LAB) isolated from infant feces were subjected to the colonization assay using C. elegans intestine. Based on coloniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thus, the ability to adhere to the host mucus layer and cells is an integral probiotic characteristic as it is a prerequisite for transient colonization (Beachey ; Ouwehand and Salminen ; Park et al . ), establishment of a functional microbial–host interaction to modulate the immune system (Erickson and Hubbard ; Delcenserie et al . ) and protection of the GIT (Tancrede ; Bernet et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ability to adhere to the host mucus layer and cells is an integral probiotic characteristic as it is a prerequisite for transient colonization (Beachey ; Ouwehand and Salminen ; Park et al . ), establishment of a functional microbial–host interaction to modulate the immune system (Erickson and Hubbard ; Delcenserie et al . ) and protection of the GIT (Tancrede ; Bernet et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, to be able to confer health benefits, these probiotics must be able to survive the harsh environment of the host gastrointestinal tract (GIT) and thrive in the intestinal mucosa (Sahadeva et al 2011). Thus, the ability to adhere to the host mucus layer and cells is an integral probiotic characteristic as it is a prerequisite for transient colonization (Beachey 1981;Ouwehand and Salminen 2003;Park et al 2013), establishment of a functional microbial-host interaction to modulate the immune system (Erickson and Hubbard 2000;Delcenserie et al 2008) and protection of the GIT (Tancrede 1992;Bernet et al 1994;Collado et al 2007a). Adhesion studies of numerous probiotic bacteria have been performed; these have also emphasized their role in preventing colon cancer (Byrd and Bresalier 2004) and enhancing the overall microbial flora by inhibiting pathogens (Salminen et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The C. elegans strain used in this study was glp-4(bn2);sek-1(km4) double mutant strain (Kim and Mylonakis, 2012). This nematode strain was routinely maintained on nematode growth medium plates seeded with Escherichia coli OP50, as described previously (Park et al, 2013).…”
mentioning
confidence: 99%
“…This animal does not present ethical issues, is inexpensive to maintain, and involves less time and labor for screening . Interestingly, the relationship between diet and longevity is an important consideration in the interpretation of assays of C. elegans life span involving modification of bacterial food source, and several studies have demonstrated that lactobacilli and bifidobacteria modify host defense and prolong the lifespan of nematodes. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…10 Interestingly, the relationship between diet and longevity is an important consideration in the interpretation of assays of C. elegans life span involving modification of bacterial food source, and several studies have demonstrated that lactobacilli and bifidobacteria modify host defense and prolong the lifespan of nematodes. 7,8,11,12 It is well-established that the interactions between C. elegans and bacteria with respect to aging and host longevity are complicated and multifactorial, 13−15 among which the neurotransmitter serotonin has long been suggested to be an important food signal in C. elegans. 16 The unifying characteristic of C. elegans serotonergic responses is the coupling of food perception to various endocrine outputs.…”
Section: ■ Introductionmentioning
confidence: 99%